2022
DOI: 10.1002/emp2.12791
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department initiated resuscitative endovascular balloon occlusion of the aorta (REBOA) for out‐of‐hospital cardiac arrest is feasible and associated with improvements in end‐tidal carbon dioxide

Abstract: Objectives Out‐of‐hospital cardiac arrest (OHCA) claims the lives of approximately 350,000 people in the United States each year. Resuscitative endovascular balloon occlusion of the aorta (REBOA) when used as an adjunct to advanced cardiac life support may improve cardio‐cerebral perfusion. Our primary research objective was to determine the feasibility of emergency department (ED)‐initiated REBOA for OHCA patients in an academic urban ED. Methods This was a single‐cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Hilbert-Carius et al 24 showed that observed mortality in 26 traumatic OHCA patients receiving REBOA early after hospital admission was 20% significantly lower than predicted by the Revised Injury Severity Score II. Three groups observed a significant increase in end-tidal CO 2 after prehospital or ER REBOA for OHCA, suggesting improved organ circulation 10,14,41,42 . A study by Cralley et al suggested that zone 1 REBOA results in similar or better survival compared with resuscitative thoracotomy, including in patients with penetrating chest injuries, traditionally considered a contraindication for REBOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilbert-Carius et al 24 showed that observed mortality in 26 traumatic OHCA patients receiving REBOA early after hospital admission was 20% significantly lower than predicted by the Revised Injury Severity Score II. Three groups observed a significant increase in end-tidal CO 2 after prehospital or ER REBOA for OHCA, suggesting improved organ circulation 10,14,41,42 . A study by Cralley et al suggested that zone 1 REBOA results in similar or better survival compared with resuscitative thoracotomy, including in patients with penetrating chest injuries, traditionally considered a contraindication for REBOA.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups observed a significant increase in end-tidal CO 2 after prehospital or ER REBOA for OHCA, suggesting improved organ circulation. 10,14,41,42 A study by Cralley et al suggested that zone 1 REBOA results in similar or better survival compared with resuscitative thoracotomy, including in patients with penetrating chest injuries, traditionally considered a contraindication for REBOA. The ongoing REBOARREST randomized clinical trial will likely provide more insights on REBOA use as ACLS adjunct for OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies report the use of REBOA in the ED for nontraumatic out of hospital cardiac arrest. 16 The REBOARREST trial is an upcoming randomized trial which will hopefully further delineate the role of REBOA in this scenario. 17 Despite the potential advantages of REBOA, there are several important disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Although these potential benefits appear promising, current evidence supporting REBOA in nontraumatic cardiac arrest remains limited. Some observational studies report the use of REBOA in the ED for nontraumatic out of hospital cardiac arrest 16 . The REBOARREST trial is an upcoming randomized trial which will hopefully further delineate the role of REBOA in this scenario 17 …”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 The feasibility of REBOA during CPR in traumatic and non-traumatic cardiac arrest is demonstrated in observational studies, with balloon deployment either in the emergency department or pre-hospital setting. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Currently, randomized controlled trials assess the efficacy of REBOA as an adjunct treatment in traumatic hemorrhage 27 and in non-traumatic out-of-hospital cardiac arrest (OHCA). 28 …”
Section: Introductionmentioning
confidence: 99%